The semiotic dimension of transmedia design - Carvalho Alzamora, Geane (InfoDesign, 2022)
This discussion is based on the following questions: a) What are the limits and potential of transmedia design for contemporary communication planning?; b) How and to what extent can semiotics contribute to the issue? In order to answer these questions, we consider that the transmedia logic outlines the contemporary communication logic. In this sense, we emphasize the necessary articulation between communication and transmedia logic to discuss the specificities of design and semiotics in the scope of transmedia logic and their implications in various areas of knowledge. We seek to highlight the etymological approach between sign and design to elucidate the contributions of semiotics to this area of knowledge. Concomitantly, it is emphasized that transmedia logic can be better understood with the adoption of the logical perspective stemming from Charles Sanders Peirce’s pragmatism, which identifies logic with semiotics.